Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.3329/bvet.v33i2.36456
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the pregnancy rate in indigenous ewes following AI using frozen semen

Abstract: Study was conducted to observe the influence of different factors on pregnancy rate in 24 indigenous ewes following artificial insemination (AI) with frozen semen. The ewes were synchronized by intra-muscular injection of Prostaglandin F2α (Ovuprost ® Bayer, New Zealand). The onset and intensity of oestrus were determined by oestrus behaviour of ewes with vasectomized ram. VER values were measured immediately before AI using electrical heat detector (DRAMINSKI ® , Owocowa 17, Poland). Twelve ewes were insemina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
2
1
0
Order By: Relevance
“…In this study, a significantly higher (p<0.05) pregnancy rate (75%) was found in ewes which were inseminated 20-24 hours from the onset of estrus. The study report is similar to Naher et al (2017) and Azizunnesa (2016), who reported a pregnancy rate of 75%-77.3% following LAP-AI, inseminated 20-24 hours from the onset of estrus.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In this study, a significantly higher (p<0.05) pregnancy rate (75%) was found in ewes which were inseminated 20-24 hours from the onset of estrus. The study report is similar to Naher et al (2017) and Azizunnesa (2016), who reported a pregnancy rate of 75%-77.3% following LAP-AI, inseminated 20-24 hours from the onset of estrus.…”
Section: Discussionsupporting
confidence: 89%
“…The pregnancy rate was significantly higher (83.33%) in ewes which were punctured 4-5 cm away from the udder, facilitating the clear visualization of the uterine horn near the puncture site. This result is similar to Naher et al (2017) and Jha et al (2020). This result is not matched with Dovenski et al (2012) and El-Badry et al (2014), found higher pregnancy rate when puncturing ewes 7-10 cm away from the udder.…”
Section: Discussionsupporting
confidence: 42%
“…Moreover, the farmers favor to practice low input technology in their extensive farming system (Bora and Das, 2013). In Bangladesh, preliminary work on artificial insemination in sheep breeding program has been performed by many researchers (Rekha et al 2016;Naher et al 2016;Jha et al 2020). Till to date, there is found no information about the cost structure of frozen ram semen as well as Developing a Cost Structure of Frozen Semen Production and Performance of Artificial Insemination for Sheep Breeding Program performance artificial insemination.…”
Section: Introductionmentioning
confidence: 99%